A latent profile analysis of intuitive eating behaviors related to wellbeing, eating behaviors, and physical activity during the early COVID-19 pandemic - Johnson, Ashlie N., author; Graham, Dan, advisor; Prince, Mark, committee member; Rickard, Kathy, committee member; Shomaker, Lauren, committee member (Colorado State University. Libraries, 2022)
Intuitive eating (IE) is a promising approach to improve eating behaviors that is primarily focused on eating in attunement with one's internal signals of hunger and satiety. Intuitive eating is related to an array of benefits including improved physical and mental health; however, many gaps exist in the IE literature. The current work utilized a novel approach in the IE context, a latent profile analysis (LPA) of 947 adults, to identify common patterns of responses to the four subscales of IE during the early COVID-19 pandemic, a time period currently understudied in the IE field. The study employed independent LPAs for two subsamples (n = 446 undergraduate students and n = 501 community members) to detect potential differences in model structure. The derived profiles were then used to test associations between COVID-19-related changes in dietary behaviors and weight concern, gender, weight loss attempts, physical activity, and mental health. LPAs of the combined sample resulted in a four-profile model. This model structure was not replicated in the undergraduate and community subsamples which showed notably different profile solutions. The two undergraduate profiles distinguished patterns of responses that were associated with lower overall (Low) and moderately high (Mod-high) levels of IE. Men were more likely to be in the Mod-High profile compared to women and the Low profile was associated with higher amounts depression, anxiety and weight loss attempts, increases in food eaten during the COVID-19 pandemic, and higher probabilities of increased weight concern during the pandemic. The community subsample showed a four-profile solution. 1: high levels of Unconditional Permission to Eat (UPE) and low levels of Eating for Physical Rather than Emotional Reasons (EPR), Reliance on Hunger and Satiety Cues (RHSC), and Body-Food Choice Congruence (B-FCC), which was related to increases in amount of food eaten, depression, and anxiety, and higher probabilities of increases in weight concern compared to the other profiles. 2: moderately high levels of UPE and very low levels of EPR, RHSC, and B-FCC, which showed the highest rates of weight loss attempts as well as high probabilities of increased weight concern. 3: moderate to high levels of all 4 IE subscales characterized by fewer weight loss attempts than profiles 1 and 2. 4: highest overall levels of IE which had the most stability in their weight concern compared to the other profiles. There were no gender differences between the four profiles of the community subsample and there were no associations with physical activity in either the undergraduate or community subsamples' profiles. These findings support the hypothesis that multiple, distinct profiles of IE exist and have unique relationships with health-related behaviors and outcomes. However, profile structures did vary between the undergraduate and community subsamples, suggesting limited generalizability between the two groups. Together, results suggest that IE levels both globally and in specific, naturally-occurring combinations of subscales are differentially related to eating and dieting behaviors, body image, and mental health. In application, findings suggest there may be benefits to recognizing varying patterns of IE to create tailored techniques for interventions seeking to increase these adaptive eating behaviors. Future research should continue to employ person-centered approaches alongside variable-centered ones to study more diverse populations and non-pandemic conditions.
Keywords: eating behaviors; latent profile analysis; COVID-19; well being; intuitive eating